MOSSES OF GUNUNG HALIMUN NATIONAL PARK, WEST JAVA, INDONESIA - Benito C Tan; Boon-Chuan Ho; Virgilio Linis; Eka A. P. Iskandar; Ipah Nurhasanah; Sri Mulyati; Ida Haerida (Research Center for Biology, 2006)
TAN, BENITO C.; HO, BOON-CHUAN; LINIS, VIRGILIO;ISKANDAR, EKA A.P.; NURHASANAH, IPAH; DAMAYANTI, LIA; MULYATI,SRI; HAERIDA, IDA. 2006. Mosses of Gunung Halimun National Park,West Java, Indonesia. Reinwardtia 12(3): 205–214.––150 species of mosses in 74 genera and 25 families are reported for the first time from Gunung Halimun National Park(GHNP)in West Java.Three mosses are new to the Indonesia flora (Distichophyllum collenchymatosum, D. malayense and Fissidens kinabaluensis),and another four mosses represent new records for Java (Dicranodontium asperulum, Daltonia armata, Glossadelphus bilobatus and Syrrhopodon semiliber).In additions, seven can be classified as uncommon mosses in the Malesian region. This shows that the forests of GHNP deserve a high priority of protection not only for the island of Java, but also for Indonesia and Malesia as well.